EFEKTIVITAS PEMBELAJARAN MELALUI GOOGLE CLASSROOM TERHADAP HASIL BELAJAR TIK SISWA SMK N 2 RAMBAH KELAS XII - Sultan Hasibuan; Jufri; Agung Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of using Google Classroom on students’ learning outcomes in Information and Communication Technology (ICT) subjects at SMK Negeri 2 Rambah. A pre-experimental method with a one-group pretest-posttest design was applied, involving 25 twelfth-grade students as the sample. Data collection instruments included multiple-choice tests to measure learning outcomes, Likert-scale questionnaires to assess students' perceptions, and supporting interviews. The findings show that the experimental class achieved an average N-Gain of 0.425 (moderate category), higher than the control class with 0.235, indicating improved learning outcomes through Google Classroom. Most students responded positively, highlighting ease of access (91.1%), practical material delivery (96.7%), and increased online interaction (84.4%). Challenges included unstable internet connections and limited device capacity. These results reinforce the role of Google Classroom as an effective and flexible digital learning medium, supporting constructivist learning theory through active and collaborative engagement. It is recommended that this platform be continuously integrated to enhance the quality of ICT learning in vocational school environments.